The intestinal microbiota and obesity - Kallus, Samuel J; Brandt, Lawrence J (Journal of clinical gastroenterology, 2012)
Obesity has been and continues to be an epidemic in the United States. Obesity has been addressed in multiple health initiatives, including Healthy People 2010, with no state meeting the proposed goal of a prevalence of obesity < 15% of the adult population. In contrast, obesity rates have continued to increase, with the self-reported prevalence of obesity among adults increasing by 1.1% from 2007 to the present. Indeed, since 2009, 33 states reported obesity prevalences of 25% or more with only 1 state reporting prevalence < 20%. There have been multiple approaches for the treatment of obesity, including fad diets, incentive-based exercise programs, and gastric bypass surgery; none of which have been optimal. In a murine model, it was shown that the majority of the intestinal microbiome consists of two bacterial phyla, the Bacteroidetes and the Firmicutes, and that the relative abundance of these two phyla differs among lean and obese mice; the obese mouse had a higher proportion of Firmicutes to Bacteroidetes (50% greater) than the lean mouse. The same results were appreciated in obese humans compared to lean subjects. The postulated explanation for this finding is that Firmicutes produce more complete metabolism of a given energy source than do Bacteroidetes, thus promoting more efficient absorption of calories and subsequent weight gain. Researchers were able to demonstrate that colonizing germ-free mice with the intestinal microbiome from obese mice led to an increased total body fat in the recipient mice despite a lack of change in diet. The converse, that, colonizing germ-free obese mice with the intestinal microbiome of thin mice causing a decreased total body fat in the recipient mice, has not yet been done. Other possible mechanisms by which the intestinal microbiome affects host obesity include induction of low-grade inflammation with lipopolysaccharide, regulation of host genes responsible for energy expenditure and storage, and hormonal communication between the intestinal microbiome and the host. The following review discusses the microbiome-obesity relationship and proposed mechanisms by which the intestinal microbiota is hypothesized to influence weight gain.